The two-dimensional XY model at the transition temperature: a high-precision Monte Carlo study - Hasenbusch, Martin (Journal of physics. A, Mathematical and general, 2005)
We study the classical XY (plane rotator) model at the Kosterlitz-Thouless phase transition. We simulate the model using the single-cluster algorithm on square lattices of a linear size up to L = 2048. We derive the finite-size behaviour of the second moment correlation length over the lattice size ξ2nd/L at the transition temperature. This new prediction and the analogous one for the helicity modulus ϒ are confronted with our Monte Carlo data. This way βKT = 1.1199 is confirmed as inverse transition temperature. Finally, we address the puzzle of logarithmic corrections of the magnetic susceptibility χ at the transition temperature.
Gesehen am 08.07.2022